Effect of red blood cell storage time in pediatric cardiac surgery patients: A subgroup analysis of a randomized controlled trialCentral MessagePerspective - Sophie M. Martin, MD; Marisa Tucci, MD; Philip C. Spinella, MD; Thierry Ducruet, MSc; Dean A. Fergusson, MHA, PhD; Darren H. Freed, MD, PhD; Jacques Lacroix, MD; Nancy Poirier, MD; Venkatesan B. Sivarajan, MD, MS; Marie E. Steiner, MD, MS; Ariane Willems, MD, PhD; Gonzalo Garcia Guerra, MD, PhD, MSc (JTCVS Open, 2023)
Objective: This study aimed to determine whether or not transfusion of fresh red blood cells (RBCs) reduced the incidence of new or progressive multiple organ dysfunction syndrome compared with standard-issue RBCs in pediatric patients undergoing cardiac surgery. Methods: Preplanned secondary analysis of the Age of Blood in Children in Pediatric Intensive Care Unit study, an international randomized controlled trial. This study included children enrolled in the Age of Blood in Children in Pediatric Intensive Care Unit trial and admitted to a pediatric intensive care unit after cardiac surgery with cardiopulmonary bypass. Patients were randomized to receive either fresh (stored ≤7 days) or standard-issue RBCs. The primary outcome measure was new or progressive multiple organ dysfunction syndrome, measured up to 28 days postrandomization or at pediatric intensive care unit discharge, or death. Results: One hundred seventy-eight patients (median age, 0.6 years; interquartile range, 0.3-2.6 years) were included with 89 patients randomized to the fresh RBCs group (median length of storage, 5 days; interquartile range, 4-6 days) and 89 to the standard-issue RBCs group (median length of storage, 18 days; interquartile range, 13-22 days). There were no statistically significant differences in new or progressive multiple organ dysfunction syndrome between fresh (43 out of 89 [48.3%]) and standard-issue RBCs groups (38 out of 88 [43.2%]), with a relative risk of 1.12 (95% CI, 0.81 to 1.54; P = .49) and an unadjusted absolute risk difference of 5.1% (95% CI, −9.5% to 19.8%; P = .49). Conclusions: In neonates and children undergoing cardiac surgery with cardiopulmonary bypass, the use of fresh RBCs did not reduce the incidence of new or progressive multiple organ dysfunction syndrome compared with the standard-issue RBCs. A larger trial is needed to confirm these results.